Effects of foliar applications of γ-polyglutamic acid and alginic acid on the quality and antioxidant activity of Marselan grapes and wines - Huawei Chen; Lijian Zhang; Bowei Yang; Miaomiao Wang; Litao Ma; Jingjing Shi; Zhenwen Zhang; Qingqing Zeng (Food Chemistry: X)
This study investigated the effects of γ-polyglutamic acid (PGA) and alginic acid (ALA) on grapes and wines. Marselan grapes were utilized to assess the accumulation and synthesis of phenolic compounds and antioxidant activity. The 0.35 % (v/v) PGA (PGA2) significantly enhanced the antioxidant activity of both grapes and wines in both years. Overall, treatments with 0.45 % (v/v) PGA (PGA3), 0.45 % (v/v) ALA (ALA3), and 0.25 % (v/v) ALA (ALA1) notably increased the total phenolic and anthocyanin content in both grapes and wines. Among these, PGA3 treatment significantly upregulated the levels of Delphinidin-3-O-(6-acetyl)-glucoside, Cyanidin-3-O-(6-acetyl)-glucoside, Peonidin-3-O-glucoside, and Malvidin-3-O-(trans-6-O-coumaryl)-glucoside in both years. Additionally, PGA3 treatment elevated the expression of the VvPAL, VvCHS, VvDFR and VvLDOX genes across both years. In contrast, ALA3 and ALA1 treatments increased anthocyanin content by upregulating the expression of VvCHS, VvF3’H and VvUFGT genes. In summary, PGA3 treatment significantly enhanced the phenolic compounds and antioxidant activity in both grapes and wines. These findings demonstrate the potential of PGA and ALA as biostimulants to significantly enhance grape and wine quality in viticulture.